Clinical Signatures of Mucinous and Poorly Differentiated Subtypes of Colorectal Adenocarcinomas by a Propensity Score Analysis of an Independent Patient Database from Three Phase III Trials. Issue 4 (April 2018) - Kanda, Mitsuro; Oba, Koji; Aoyama, Toru; Kashiwabara, Kosuke; Mayanagi, Shuhei; Maeda, Hiromichi; Honda, Michitaka; Hamada, Chikuma; Sadahiro, Sotaro; Sakamoto, Junichi; Saji, Shigetoyo; Yoshikawa, Takaki
Abstract : BACKGROUND: Although colorectal cancer comprises several histological subtypes, the influences of histological subtypes on disease progression and treatment responses remain controversial. OBJECTIVE: We sought to evaluate the prognostic relevance of mucinous and poorly differentiated histological subtypes of colorectal cancer by the propensity score weighting analysis of prospectively collected data from multi-institute phase III trials. DESIGN: Independent patient data analysis of a pooled database from 3 phase III trials was performed. SETTINGS: An integrated database of 3 multicenter prospective clinical trials (the Japanese Foundation for Multidisciplinary Treatment of Cancer 7, 15, and 33) was the source of study data. INTERVENTIONS: Surgery alone or postoperative adjuvant chemotherapy was offered in patients with resectable colorectal cancer. MAIN OUTCOME MEASURES: To balance essential variables more strictly for the comparison analyses, propensity score weighting was conducted with the use of a multinomial logistic regression model. We evaluated the clinical signatures of mucinous and poorly differentiated subtypes with regard to postoperative survival, recurrence, and chemosensitivity. RESULTS: Of 5489 patients, 136 (2.5%) and 155 (2.8%) were pathologically diagnosed with poorly differentiated and mucinous subtypes. The poorly differentiated subtypes were associated with a poorer prognosis than the "others" group (HR, 1.69; 95% CI, 1.00–2.87; p = 0.051), particularly in the patient subgroup of adjuvant chemotherapy (HR, 2.16). Although the mucinous subtype had a marginal prognostic impact among patients with stage I to III colorectal cancer (HR, 1.33; 95% CI, 0.90–1.96), it was found to be an independent prognostic factor in the subpopulation of patients with stage II disease, being associated with a higher prevalence of peritoneal recurrence. LIMITATIONS: The treatment regimens of postoperative chemotherapy are now somewhat outdated. CONCLUSIONS: Both mucinous and poorly differentiated subtypes have distinct clinical characteristics. Patients with the mucinous subtype require special attention during follow-up, even for stage II disease, because of the risk of peritoneal or local recurrence. SeeVideo Abstract athttp://links.lww.com/DCR/A531 . Abstract : Supplemental Digital Content is available in the text.